PREDIKSI JUMLAH MAHASISWA BARU FMIPA-K UNIMA MENGGUNAKAN MODEL REGRESI NON-LINEAR - Lengkong, Ningsi M.; Langat, Rahel A.; Parapaga, Eka; Tetiwar, Geraldo; Tuerah, Auriel; Pangemanan, Tamariska; Mangobi, James U. L.; Maukar, Marvel G. (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to forecast the number of new students in each study program within the Faculty of Mathematics, Natural Sciences, and Earth Sciences at Manado State University (UNIMA) using a nonlinear regression model, specifically a polynomial model, based on historical enrollment data from the past five years. Accurate forecasting is expected to significantly support more strategic planning in creating a better campus environment and improving the comfort of future prospective students. The data in this study were processed using Microsoft Excel software by developing a third-order polynomial model, selected based on the coefficient of determination (R-squared) as the most suitable fit for the available data. The results indicate that the number of new students in each study program at FMIPA-K UNIMA is projected to increase significantly over the next ten years. This research can serve as a valuable reference for the faculty and study programs to anticipate future enrollment trends.